2018
DOI: 10.1111/jce.13737
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of ryanodine receptor 2 phosphorylation in the effect of azumolene on ventricular arrhythmia vulnerability in a rabbit heart model

Abstract: Ventricular refibrillation following LDVF was reduced by azumolene, which also improves calcium dynamics. RyR2 phosphorylation at Ser2808 is a prerequisite for the beneficial effects of azumolene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 39 publications
(79 reference statements)
0
18
0
Order By: Relevance
“…Aberrant phosphorylation of RyR2 has been linked to atrial fibrillation (Chiang et al, 2014;Si et al, 2018), heart failure (Dobrev and Wehrens, 2014;Marx et al, 2000;van Oort et al, 2010), increased cell death in ischemia-reperfusion (Di Carlo et al, 2014), cognitive dysfunction (Liu et al, 2012), and Alzheimer's disease (Lacampagne et al, 2017), although the exact molecular mechanisms are heavily disputed (Bers, 2012;Eschenhagen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant phosphorylation of RyR2 has been linked to atrial fibrillation (Chiang et al, 2014;Si et al, 2018), heart failure (Dobrev and Wehrens, 2014;Marx et al, 2000;van Oort et al, 2010), increased cell death in ischemia-reperfusion (Di Carlo et al, 2014), cognitive dysfunction (Liu et al, 2012), and Alzheimer's disease (Lacampagne et al, 2017), although the exact molecular mechanisms are heavily disputed (Bers, 2012;Eschenhagen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, which used azumolene, an active analog of dantrolene, we demonstrated that the phosphorylation of RyR2 is essential for azumolene function in ischemia and long-duration ventricular fibrillation. 24 The cardioprotective effect of dantrolene has also been demonstrated in various acute and chronic models of DICM, 29,30 but these previous studies did not assess the impact on calcium dynamics as demonstrated in this study.…”
Section: Dantrolene and Cardiac Contractile Functionmentioning
confidence: 72%
“…For calcium transient duration (CaTD) analysis, 0 to 50% of repolarization (CaTD 50 ) and 0 to 80% of repolarization (CaTD 80 ) were analyzed, as described previously. 23,24 Calcium amplitude alternans ratio analysis Ca 21 amplitude alternans refers to the beat-to-beat difference of Ca 21 signal amplitudes during cardiac stimulation. A calcium amplitude alternans ratio (CaAAR) of 1 indicates similar amplitudes, whereas a ratio of 0.5 refers to a 50% difference between large and small Ca 21 amplitudes.…”
Section: Calcium Transient Duration Analysismentioning
confidence: 99%
See 2 more Smart Citations